Analisis dampak pembelajaran matematika berbantuan media youtube terhadap kemampuan berpikir kreatif siswa kelas V sekolah dasar selama social distancing - Kusuma Ridho Fadillah; Sri Marmoah; Hadiyah Hadiyah (Universitas Sebelas Maret, 2021)
This research aims to describe the impact of larning mathematics assisted by youtube media on the creative thinking skills of elementary school students during social distancing. The subject of this research were the teacher and 26 students from 5th grade of state primary school at Surakarta on the 2020/2021 academy year. The data collection technique in this research are interview, observation, questionnaires, and test. By using four indicators of creative thinking skills, the result showed that one of the four indicators was in the moderate category. This indicator is flexibility. Three of the four indicators are in the high category. This shows that learning mathematics assisted by youtube media has a good impact on the creative thinking skills of elementary school students during social distancing.